2022
DOI: 10.2196/34285
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media to Predict Food Deserts in the United States: Infodemiology Study of Tweets

Abstract: BackgroundThe issue of food insecurity is becoming increasingly important to public health practitioners because of the adverse health outcomes and underlying racial disparities associated with insufficient access to healthy foods. Prior research has used data sources such as surveys, geographic information systems, and food store assessments to identify regions classified as food deserts but perhaps the individuals in these regions unknowingly provide their own accounts of food consumption and food insecurity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In this study, we found that COVID-19 vaccine attitudes in the HPS, measured as vaccine compliance and hesitancy, can be predicted using social media attitudes toward vaccines, measured via sentiments and emotions toward vaccines. The results of this study support the efforts of researchers, who over the past few years have looked at social media as a data source, citing the availability of readily available data and no-or low-cost data collection efforts [40,41].…”
Section: Study Findings In Contextsupporting
confidence: 74%
“…In this study, we found that COVID-19 vaccine attitudes in the HPS, measured as vaccine compliance and hesitancy, can be predicted using social media attitudes toward vaccines, measured via sentiments and emotions toward vaccines. The results of this study support the efforts of researchers, who over the past few years have looked at social media as a data source, citing the availability of readily available data and no-or low-cost data collection efforts [40,41].…”
Section: Study Findings In Contextsupporting
confidence: 74%
“…Some tweets also addressed concerns related to altered or extreme climatic conditions, particularly the potential health impacts of extreme heat. Given innovative studies that utilize Twitter data to identify geographical dynamics or food deserts associated with inadequate access to healthy food [54,55] and the growing need for research to focus on charity food supply options in rural areas these aspects merit further investigation. Additionally, the risks posed by the climate crisis, particularly for socioeconomically disadvantaged groups, should be integrated more extensively into public health research.…”
Section: Discussionmentioning
confidence: 99%
“…The work on both terms is taken into account here, but in the further course of the data analysis reference is made exclusively to the theoretical assumptions on food poverty [10,19]. Some social media-related studies on food insecurity or poverty have analysed food-related tweets and metadata to identify geographical dynamics or food deserts associated with inadequate access to healthy foods [54,55]. Other studies have focused on sentiment analysis to examine emotions or reactions expressed on Twitter, particularly in response to emergency food supplies [56].…”
Section: Social Media As a Voice Amplifier For Food Poverty Experiencesmentioning
confidence: 99%
“…Previous studies have used a variety of NLP techniques as part of an infodemiological process to explore different areas of food security for different purposes; however, they have not combined sentiment and topic analysis across time and in relation to social media engagement, as in this study. Studies have used NLP to predict food deserts using the sentiment and nutritional value of the foods mentioned on social media within different geographic regions [73] and to summarize the academic literature on community gardens [74]. Research similar to this study includes a study by Mayasari et al [75] that used Google Trends to explore food security and dietary and lifestyle behaviors during the COVID-19 pandemic.…”
Section: Comparison With Prior Workmentioning
confidence: 99%